Phylogenetic Implications and Functional Disparity in the Chalcone synthase Gene Family of Common Seagrass Zostera marina - Ma, Mingyu; Zhong, Mingyu; Zhang, Quansheng; Zhao, Wei; Wang, Mengxin; Luo, Chengying (Frontiers in Marine Science, 2021)
Chalcone synthase (CHS) family are plant type III polyketide synthases that participate in the flavonoid synthesis pathway to induce plant resistance to various biotic and abiotic stresses. Zostera marina, a common seagrass, migrated to terrestrial conditions and returned to the sea, achieving the most severe habitat shift of flowering plants. Given the special evolutionary process, we conducted genome-wide, expression and enzyme activity analyses of the ZosmaCHS family to understand its phylogenetic implications. Various duplication modes led to the expansion of 11 CHS homologues in Z. marina. Based on the phylogenetic relationships, ZosmaCHSs were classified into three clades. Further quantitative real time-PCR analyses of the ZosmaCHS homologues showed different light responses and tissue-specific expression, indicating functional diversification of the ZosmaCHSs. Moreover, the ZosmaCHS proteins clustering with the validated chalcone synthases were recombined into prokaryotic expression systems. All the recombinant proteins showed CHS activity to generate naringenin chalcone with varying catalytic efficiencies. ZosmaCHS07 was regarded as the dominant CHS because of its significant light response and the higher catalytic efficiency. Taken together, the disparity of the expression and enzyme activity indicated that sub-functionalization is the primary mechanism of the expansion of the ZosmaCHSs family.